Anatomical preconditions for the palatal sinus floor augmentation—A three-dimensional feasibility study. Issue 7 (September 2015) - Wagner, F.; Dvorak, G.; Pillerstorff, R.; Traxler, H.; Nemec, S.; Pietschmann, P.; Seemann, R.
Abstract Objective The aim of this study was to evaluate the anatomical feasibility of palatal sinus floor augmentation. Material and methods In 100 men and 100 women, both sinuses were analyzed using computed tomography. The patients were divided into four anatomical groups according to the remaining alveolar bone height: group 1 (0 ≤ × < 4), group 2 (4 ≤ × < 8), group 3 (8 ≤ × < 12), and group 4 (≥12). Results The 400 maxillary sinuses consisted of 23.5% (n = 94) group 1, 42.75% (n = 171) group 2, 23.5% (n = 98) group 3, and 9.25% (n = 37) group 4 sinuses. Optimal anatomical preconditions for palatal sinus floor augmentations (i.e., ≥5 mm height and <5 mm thickness of the window lid) were found in 93.6% of group 1 sinuses, 73.7% of group 2 sinuses, 23.5% of group 3 sinuses, and 5.4% of group 4 sinuses. Conclusion The palatal approach is feasible in 93.6% of patients with remnant alveolar height of up to 4 mm. Limitations are alveolar heights of ≤5 mm as well as great palatal thickness and thus limited dimensions for a possible palatal window.